The MicroRNA-106a/20b Strongly Enhances the Antitumour Immune Responses of Dendritic Cells Pulsed with Glioma Stem Cells by Targeting STAT3 - Hui Zhou; Chengmei Sun; Cong Li; Shiting Hua; Feng Li; Ruichun Li; Dongpeng Cai; Yuxi Zou; Yingqian Cai; Xiaodan Jiang (Journal of Immunology Research)
Background. Evaluate the effect of the miRNA-106a/20b on the efficacy of DCs pulsed with GSCs in activating GSC-specific T cell responses. Methods. We cultured GSCs and prepared GSC antigen lysates by apoptosis. Then, immature DCs were pulsed with GSC antigen lysates in vitro. STAT3 levels in DCs were assessed by Western blotting, and the expression of CD80, CD86, and MHC-II was tested by fluorescence-activated cell sorting. The production and secretion of the cytokines IL-6, IL-12, TNF-α, and IL-10 in DCs induced by GSCs were determined by enzyme-linked immunosorbent assay. Finally, the cytotoxic functions of T cells stimulated by GSC-DC fusion cells transfected with a miR-106a/20b mimic in vitro and the antitumour activity in vivo were detected. Results. We found that the levels of miR-106a/20b were downregulated, but the expression of STAT3 was significantly upregulated. Simultaneously, the inhibition of STAT3 in the fusion cells by STAT3-specific siRNA caused significant upregulation of the expression of CD80, CD86, and MHC-II, and the secretion of the cytokines IL-6 and IL-12 was substantially increased, IL-10 was markedly decreased. These findings revealed that STAT3 is an important regulator of DC maturation. Furthermore, the interactional binding sites between the 3′-untranslated region (3′-UTR) of STAT3 mRNA and miR-106a/20b were predicted by bioinformatics and verified by a dual-luciferase assay. Moreover, the reduction in STAT3 levels in GSC-DCs enhanced the generation of CD8+ T cells and reduced the generation of Foxp3+ regulatory T cells. Meanwhile, the secretion of the T cell cytokine IFN-γ was significantly increased. Further research showed that DCs after miR-106a/20b-mimics transfection could promote the inhibition of GSC proliferation by T cells in vitro and suppress tumour growth in vivo. Conclusions. This study indicted that the miR-106a/20b activation could be one of the important molecular mechanisms leading to enhance antitumour immune responses of GSC-mediated DCs, which downregulated the expression of STAT3 to alleviate its the inhibitory effect.